Heterocycle/heteroallene ring opening copolymerisation: selective catalysis delivering alternating copolymers - Williams, CK; Plajer, A (Wiley, 2021)
Heteroatom containing polymers have strong potential as sustainable replacements for petrochemicals, show controllable monomer-polymer equilibria and properties spanning plastics, elastomers, fibres, resins, foams, coatings, adhesives and self-assembled nanostructures. Their current and future applications span packaging, house-hold goods, clothing, automotive components, electronics, optical materials, sensors and medical products. An interesting route to these polymers is the catalysed ring-opening copolymerisation (ROCOP) of heterocycles and heteroallenes. It is a living polymerization, occurs with high atom economy and creates precise, new polymer structures inaccessible by traditional methods. In the last decade there has been renaissance in research and increasing examples of commercial products made using ROCOP. It is better known in the production of polycarbonates and polyesters but is also a powerful route to make N-, S- and other heteroatom containing polymers, including polyamides, polycarbamates, polythioesters and others. This review presents an overview of the different catalysts, monomer combinations and polymer classes accessed by heterocycle/heteroallene ROCOP. It aims to provide a guide for users both to the catalysis and the resulting materials properties as well as highlighting opportunities for future research and applications.